Islam and Local Culture: The Practice of Hippun Tradition Among the Lampungnese Muslims - Badi'ah, Siti; Ruslan, Idrus; Huzaimah, Siti (KALAM, 2021)
Although relation between Islam and culture has been a subject of many studies, our understanding of it is still problematic. Islam and local culture are often seen as two separated entities. In reality however, many local customs practiced by Muslim societies are loaded with values of Islamic teachings. Hippun, a tradition practiced by local Muslims in Lampung, South Sumatera, is the case in point. While Hippun is arguably rich with Islamic values, many people considered it as not Islamic. In order to enlighten the controversy, this paper is aimed at exploring the practice of Hippun tradition as well as examining its contribution to the development of Islamic moral values in Lampung societies. Based on a qualitative and descriptive research, this paper finds out that Hippun tradition consists of four processes, namely, Buwarah, Hippun Muari, Hippun Pemekonan, and Adat Hippun. During these processes a collection of rituals such as vocalizing shalawat, reciting Yasin verses from the Qur’an, prayer chanting, and incense burning was carried out. Hippun has contributed to the spread and maintenance of Islamic and social values such silaturahmi (sociability), brotherhood, musyawarah (deliberation), and social integration. It finally concludes that Hippun is a testament to the existence of acculturation between Islam and local culture in Lampung societies.